Arthrodesis of the Distal Two Tarsal Joints in the Horse Using Perforated Stainless Steel Cylinders and Cancellous Bone Graft - Schneider, R. K.; Archer, R. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
Two perforated stainless steel cylinders and autogenous cancellous bone were implanted into each of the distal intertarsal and tarsometatarsal joints of seven horses. In two control horses holes were drilled into each joint and autogenous cancellous bone was implanted without stainless steel cylinders. Horses which had cylinders implanted in the distal tarsal joints exhibited less lameness and were more comfortable following surgery than were the control horses. Fracture of the third tarsal, central tarsal, or third metatarsal occurred in five of the seven horses implanted with stainless steel cylinders within 45 days of surgery. Two implanted horses and two control horses were observed for five months after surgery. Partial fusion of the distal tarsal joints occurred in all four horses. Control horses were more lame than the implanted horses and developed a large bony exostosis over the medial distal tarsus.
Keywords: Arthrodesis; tarsus; horse; bone spavin; stainless steel cylinders